COMPARATIVE ANALYSIS OF ROBOCONSTRUCTION KITS TO INCREASE THE EFFICIENCY OF TRAINING - Kenesbaev С.М.; Shaiken А.Ғ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article provides a systematic and thematic overview of the collection of robotics for schoolchildren (non-social robots), existing robotics tools. That is, the main areas of application, features and importance of the robotic kit are discussed. The types of kits for the construction of robots and the details of the kit are being specified. In addition, the use of constructive approaches to analyze student participation in robotics education is explored in the development and implementation of robotics curricula. It is shown what kind of robot can be assembled from sets of robot constructors. Demonstrates the impact of robot design kits on the development of students’ interests and abilities. Based on the results of the study, it is recommended to determine the knowledge of robotics in relation to computer science and indicate the set of knowledge, skills and robotics that can be developed with the help of robotics. In addition, the designer of the robot assumes that the choice should depend on the quality of the kits, the size of the parts, and the safety of working with them. In general, the article concludes that, depending on the type of robot-constructor, it is necessary to take into account the age characteristics of the student, the direction of interest. To this end, this study proposes the development of students’ design skills, professional knowledge, interest in engineering and technical sciences, taking into account their types, areas of application, features, for understanding robotics.